Human Capital Development: New Evidence on the Production of Socio-Emotional Skills - Mark Mitchell; Marta Favara; Catherine Porter; Alan Sanchez (Institute of Labor Economics (IZA), 2020)
We estimate a dynamic model of multidimensional human capital development from childhood through adolescence and into early adulthood for a Peruvian cohort born in 1994. We exploit multiple measures of cognitive and socio-emotional skills and a latent factor structure to estimate flexible skills production functions between the ages of 8 and 22. We focus particularly on socio-emotional skill development, and provide the first estimates of such skill production over such a long period in a developing country context. In the last period, when individuals reach adulthood at age 22, we show that socio-emotional skills can be separated into two distinct domains - social skills and task effectiveness skills- which develop differently especially with regard to time use and cross-productivity with cognition. We find that individuals with higher task effectiveness are less likely to have engaged in risky behaviours such as smoking, taking drugs, and engaging with gangs.
Keywords: C38; J13; J24; O15; O54; 330; human capital; child development; dynamic factor analysis; socio-emotional skills